Decolonizing History Education through Digitalization: The Role of Website-Based History Writing Projects in Validating Local Knowledge and Shaping Historical Awareness - Karina Wanda; Wiene Surya Putra (Academica: Journal of Multidisciplinary Studies, 2025)
This study examines the role of website-based digital history writing in advancing the decolonization of history education within the Primary Teacher Education Program (PGSD). Grounded in a qualitative descriptive approach, the research involved 40 second-year PGSD students participating in a semester-long digital history project that emphasized local historical inquiry, archival research, and digital storytelling. Data were collected through participatory observation, in-depth interviews, and analysis of student-produced website content and reflective journals. The findings indicate that digital history projects facilitate the validation of local knowledge by enabling students to critically juxtapose colonial archives with oral and community-based sources. This process contributed to a significant transformation in students’ historical consciousness, shifting from traditional and exemplary orientations toward critical and genetic levels. Moreover, the integration of website media fostered digital literacy, ethical awareness, and reflective historical thinking, positioning students as active producers rather than passive consumers of historical narratives. Despite challenges related to digital inequality and ethical representation, the study demonstrates that digitalization, when aligned with decolonial pedagogy, offers a powerful framework for developing inclusive and contextually grounded history education. The findings underscore the potential of digital platforms to support epistemic justice and to prepare future elementary teachers to implement decolonized history learning in schools.